2006
DOI: 10.1177/0310057x0603400512
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Observational Study of the Effect of Night Duty on the Cognitive Function of Anaesthetic Registrars

Abstract: The issue of fatigue in hospital medical staff represents a potential health and safety risk to both staff and patients, and is receiving worldwide interest. We aimed to characterize the cognitive performance of anaesthetic registrars before and after a series of night shifts. We enrolled nine full-time anaesthetic trainees in an Australian adult tertiaryreferral hospital. We conducted a cross-over observational study which tested cognitive performance in participants before and after seven consecutive night s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 18 publications
1
14
0
Order By: Relevance
“…There is evidence from studies in adults, 3 children 4,5 and neonates 6–10 that the standard of patient care after‐hours is inferior to that during working hours. The reasons for this circadian variation in outcomes include the presence of junior, less‐experienced in‐house staff after‐hours 3,11,12 and worse cognitive performance of staff at night 13,14 . Lee et al .…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence from studies in adults, 3 children 4,5 and neonates 6–10 that the standard of patient care after‐hours is inferior to that during working hours. The reasons for this circadian variation in outcomes include the presence of junior, less‐experienced in‐house staff after‐hours 3,11,12 and worse cognitive performance of staff at night 13,14 . Lee et al .…”
Section: Introductionmentioning
confidence: 99%
“…Griffiths et al found a decline in cognitive performance in anaesthetic registrars after seven nightshifts, using a computerized assessment test. 11 A decreased reaction time on a computer model by anaesthetists after night duty has also been demonstrated. 12 Of special concern and public interest is the relationship between extended work hours and the incidence of motor vehicle accidents, near misses and falling asleep while driving caused by fatigue in medical staff.…”
Section: Discussionmentioning
confidence: 89%
“…19 Griffiths et al found a significant deterioration in reaction times of anaesthetic registrars after two consecutive night shifts, but no decrease in monitoring, memory or learning speed or accuracy. 12 Other emergency-based studies have found slower time to intubation, reduced performance on intelligence testing and deterioration in memory during night shifts. [15][16][17] Our study is unique in evaluating the impact of fatigue on psychomotor performance in the context of working night shifts in a modern Australian ED.…”
Section: Discussionmentioning
confidence: 97%
“…Medical staff fatigue and its implications for patient safety, medical officer's health and safe rostering practices has become an important issue for the medical community. [1][2][3][4][5][6] Studies of fatigue in medicine have mainly focused on doctors working extended shifts or on-call shifts [7][8][9][10][11][12][13][14] and few studies have addressed fatigue in emergency doctors. [15][16][17][18][19] A chief problem in studying fatigue is objectively measuring its effects.…”
Section: Introductionmentioning
confidence: 99%